Hot Deformation Behavior and Processing Map of Ti-6Al-3Nb-2Zr-1Mo Titanium Alloy. Issue 4 (April 2016) - Chen, Haisheng; Liu, Xianghong; Liu, Guangfa; Tang, Xiaodong; Luo, Jinhua; Feng, Yong; Li, Jinshan; Fu, Hengzhi
Abstract: The isothermal compression tests were performed over the ranges of temperatures 820∼1060 °C and strain rates 0.001∼1 s −1 on a Gleeble-3800 simulator. The constitutive equation of Ti-6Al-3Nb-2Zr-1Mo alloy has been established to describe the changing rule of flow stress with the strain rate and deformation temperature. The apparent activation energies have been calculated to be 764.71 kJ/mol in the dual phase region and 126.94 kJ/mol in the single phase region. The processing maps have been constructed based on the dynamic material model (DMM) and the Prasad's instability criterion at strains of 0.4 and 0.7. The maps exhibit a stable domain in the temperature range of 840∼1060 °C and strain rate range of 0.001∼0.1 s −1 with two peaks in power dissipation of 51%, occurring at 940 °C/0.001 s −1 and 880 °C/1 s −1, respectively. The high efficiency values of power dissipation indicate dynamic recrystallization (DRX)/globalization in these fields. Based on the constructed processing maps, the optimal hot processing window of this alloy corresponds to the temperature range of 840∼1060 °C and the low strain rate range of 0.001∼0.1 s −1 . The microstructures of the specimens deformed at different conditions were analyzed and connected with the processing map. It is found that in processing of the alloy at 820 °C and a higher strain rate (≥1 s −1 ) an instability deformation will take place easily.